Role of Corporate Communication in Boomerang - Sharma, Neha (European Journal of Economics and Business Studies, 2018)
Purpose – The study tries to analyze the trends in alumni relations and the role of corporate communication in developing organizational identification and a positive boomerang behavior intention among former employees. The approach of the study has been from the point of view of making this process formal and emphasize on the impact of corporate communication in maintaining alumni relationships, and attracting the former talent for the organization. Methodology- An exploratory methodology was designed to capture the perceptions of current and former employees of nine multinational companies (MNCs) in India, on alumni communication practices prevailing in their organizations. Transcripts of semi-structured interviews were analyzed, coded thematically and the essence of experiences was jointly combined into one description. Findings – Study showed that corporate alumni website, personalized messages on discounts on products and services, emails, social networking platforms, alumni engagement events, leadership and value training workshops and corporate communication standards, particularly consistency, have a positive impact on organizational identification and finally inspire the former employees to rejoin the organization. Practical implications – A number of significant managerial implications are drawn from this study, for example using both corporate communication and training to influence former employees’ attitudes and decision to participate in volunteering activities or rejoin the previous employer. Still, it should be noted that the effect of corporate communication on the behaviors of former employees depend on communication standards and HR interventions in maintaining relationships with alumni. Originality/value – The results provide valuable insights from the key former and current employees perspectives into the effectiveness of alumni communication process to facilitate the recruitment of high performing employees or their involvement in other mutually beneficially activities . Further rehiring alumni is one such innovative method which when done in the right manner can provide a quick solution to the talent crunch. Paper type: Research paper